Identification of Occupational Safety and Health Hazards with Job Safety Analysis (JSA) Method for Paper Core Factory Workers - Saputra, Dwi Arwandi Yogi; Perdini, Fitriana Titis; Harjono, Yanti; Savitri, Pritha Maya (Symbiohealth, 2025)
This study aims to analyze occupational hazards and health risks among Paper Core factory workers, with a particular focus on occupational diseases, especially hypertension. The research is grounded in Government Regulation No. 88 of 2019 concerning occupational health and the relevance of work-related diseases to worker safety and productivity. The study employed the Hazard Identification and Risk Assessment (HIRA) and Job Safety Analysis (JSA) approaches, with risk analysis based on the AS/NZS 4360:2004 standard. Data were collected through observation, interviews, blood pressure measurement, and source triangulation. The findings indicate that workers are exposed to multiple risk factors, including workplace temperatures exceeding 30°C, noise levels up to 103.7 dB, dust exposure, adhesive chemicals, and heavy physical workloads. Among the 74 workers examined, 20 were diagnosed with hypertension. The analysis suggests that prolonged exposure to heat and noise significantly contributes to hypertension risk, although lifestyle factors and individual health history also play a role. Furthermore, suboptimal production facility layout was found to increase ergonomic and occupational safety risks. The study concludes that hypertension can be classified as an occupational disease among Paper Core factory workers. Implementation of risk management, improvement of facility layout, consistent use of personal protective equipment (PPE), and routine application of JSA are recommended to reduce occupational hazards and enhance both worker safety and productivity.